2009
DOI: 10.1371/journal.pone.0004298
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of S100B Urinary Testing at Birth in Full-Term Asphyxiated Newborns to Predict Neonatal Death

Abstract: BackgroundNeonatal death in full-term infants who suffer from perinatal asphyxia (PA) is a major subject of investigation, since few tools exist to predict patients at risk of ominous outcome. We studied the possibility that urine S100B measurement may identify which PA-affected infants are at risk of early postnatal death.Methodology/Principal FindingsIn a cross-sectional study between January 1, 2001 and December 1, 2006 we measured S100B protein in urine collected from term infants (n = 132), 60 of whom suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…While the magnitude and speed of increase in S100B levels are unknown for asphyxiated pinnipeds, a previous study 6 found that severely brain-damaged asphyxiated human neonates had urinary S100B concentrations 30-60 times higher than normal neonates, and a concentration of >1.0 μg/l was 100% specific and sensitive for a fatal outcome. Urine levels exceeded this cutoff at the first postnatal urination, implying a rapid shift of S100B from the serum into the urine.…”
Section: Research-article2013mentioning
confidence: 96%
“…While the magnitude and speed of increase in S100B levels are unknown for asphyxiated pinnipeds, a previous study 6 found that severely brain-damaged asphyxiated human neonates had urinary S100B concentrations 30-60 times higher than normal neonates, and a concentration of >1.0 μg/l was 100% specific and sensitive for a fatal outcome. Urine levels exceeded this cutoff at the first postnatal urination, implying a rapid shift of S100B from the serum into the urine.…”
Section: Research-article2013mentioning
confidence: 96%
“…Several candidates from adult traumatic brain injury studies have been investigated as potential NE biomarkers [2,3]. These include protein S100-B (S100B) [4] and neuron-specific enolase. Both appear to correlate with HI severity and neurodevelopmental outcome, but are also elevated in conditions other than HI [5].…”
Section: Doi: 101159/000490393mentioning
confidence: 99%
“…Qian et al [89] reported elevated levels of this protein in neonates with hypoxic-ischemic encephalopathy. Gazzolo et al [90] demonstrated that a high concentration of S100 had a sensitivity of 91.3% and a specificity of 94.6% for predicting the development of hypoxicischemic encephalopathy.…”
Section: Predictors Of Long-term Neurodevelopmen-tal Outcome Followinmentioning
confidence: 99%